2020
DOI: 10.1021/acscatal.0c00220
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I) or Gold(III) as Real Intermediate Species in Gold-Catalyzed Cycloaddition Reactions of Enynal/Enynone?

Abstract: Metal-bound isobenzopyrylium species are proposed as reactive intermediates in transition-metal-catalyzed [3 + 2] or [4 + 2] cyclizations of o-alkynylbenzaldehydes (enynals) or o-alkynylarylketones (enynones). Because of their high reactivity, isolation and structural characterization of such intermediates have remained elusive. Herein, we report the isolation of such gold­(I)- and gold­(III)-bound isobenzopyrylium intermediates, and two of them have been characterized by X-ray diffraction analysis. When react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…The observation of a product arising from the coupling of two alkynes within the coordination sphere of gold is remarkable. Although related pyrylium salts have been frequently proposed in the gold-catalyzed intramolecular coupling of alkynes with tethered carbonyl groups, , and may be isolated, the observation of 12 is a unusual example of an intermolecular addition and may offer the potential for future synthetic findings.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of a product arising from the coupling of two alkynes within the coordination sphere of gold is remarkable. Although related pyrylium salts have been frequently proposed in the gold-catalyzed intramolecular coupling of alkynes with tethered carbonyl groups, , and may be isolated, the observation of 12 is a unusual example of an intermolecular addition and may offer the potential for future synthetic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Oh reported the intramolecular [3 + 2] annulation of eneyne-carbonyls catalyzed by a rhodium­(I)/dppp [1,3-bis­(diphenylphosphino)­propane] complex in the presence of water, which involves hydrolysis of the rhodium­(I) carbenoids (Figure b, Type A) . Recently, our research group reported that the enantioselective intramolecular [4 + 2] annulation of eneyne-carbonyls proceeds by using a cationic gold­(I)/H 8 –BINAP [2,2′-bis­(diphenylphospino)-5,5′,6,6′,7,7′,8,8′-octahydro-1,1′-binaphthyl] complex as a catalyst in the absence of water (Figure b, Type B). , From these reports, it was revealed that both the [3 + 2] and [4 + 2] annulations proceed depending on catalysts, substrates, and reaction conditions, although detailed mechanisms have not been elucidated . Moreover, further cascade reactions are expected to be developed by the precise substrate design …”
mentioning
confidence: 99%
“…86 One way to increase the reactivities of alkynes is through the participation of a neighboring group. 87−90 Recent progress on intramolecular reactions of alkynes with neighboring aldehydes, 91,92 ketones, 91,93−96 carboxylic acids, 97−99 esters, 100−102 amides, 85,103−107 imidates, 108 or alcohols 109−112 to yield various addition products has been reported (Scheme 1). The issue of regioselectivity, often observed in the reactions of internal alkynes, is also improved by the participation of neighboring groups.…”
mentioning
confidence: 99%
“…However, fewer reports have described the reactions of alkynes catalyzed by metal-free, Lewis or Brønsted acids/bases, although these protocols could be more economical, easy to handle, and environmentally benign. , The lack of experimentation in this area is probably due to the disadvantages of metal-free, acid/base-catalyzed reactions, such as high temperature, long reaction time, , and high catalyst loading . One way to increase the reactivities of alkynes is through the participation of a neighboring group. Recent progress on intramolecular reactions of alkynes with neighboring aldehydes, , ketones, , carboxylic acids, esters, amides, , imidates, or alcohols to yield various addition products has been reported (Scheme ). The issue of regioselectivity, often observed in the reactions of internal alkynes, is also improved by the participation of neighboring groups. It is also interesting to note that under basic conditions ( o -arylethynyl)­benzyl alcohols 1 undergo cyclization via a 5- exo-dig pathway .…”
mentioning
confidence: 99%